2022
DOI: 10.4018/jgim.295450
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Security Management Countermeasures in the Prevention and Control of Computer Network Crime

Abstract: This paper aims to study the Countermeasures of big data security management in the prevention and control of computer network crime in the absence of relevant legislation and judicial practice. Starting from the concepts and definitions of computer crime and network crime, this paper puts forward the comparison matrix, investigation and statistics method and characteristic measure of computer crime. Through the methods of crime scene investigation, network investigation and network tracking, this paper studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Knowledge sharing is crucial in maximizing employee awareness and is an important indication of IS involvement. It provides real-time problem-solving and reduces the wasted effort, time, and cost associated with replicating the same solutions for similar problems (Wang, 2022;Żywiołek et al, 2021). However, Pham et al (2021) found that many participants did not see IS knowledge sharing with peers as necessary.…”
Section: Information Security Knowledge Sharingmentioning
confidence: 99%
“…Knowledge sharing is crucial in maximizing employee awareness and is an important indication of IS involvement. It provides real-time problem-solving and reduces the wasted effort, time, and cost associated with replicating the same solutions for similar problems (Wang, 2022;Żywiołek et al, 2021). However, Pham et al (2021) found that many participants did not see IS knowledge sharing with peers as necessary.…”
Section: Information Security Knowledge Sharingmentioning
confidence: 99%
“…Research has shown that securing centralized databases is a costly and challenging task for most organizations (Ngwenyama et al, 2021;Wang, 2021). Due to paucity of appropriate security mechanisms, it is common for personal information stored in central databases to get compromised through security breaches.…”
Section: Introductionmentioning
confidence: 99%